2007
DOI: 10.2151/jmsj.85.255
|View full text |Cite
|
Sign up to set email alerts
|

An Assimilation and Forecasting Experiment of the Nerima Heavy Rainfa11 with a Cloud-Resolving Nonhydrostatic 4-Dimensional Variational Data Assimilation System

Abstract: The Meteorological Research Institute of the Japan Meteorological Agency has developed a cloudresolving nonhydrostatic 4-dimensional variational assimilation system (NHM-4DVAR), based on the Japan Meteorological Agency Nonhydrostatic Model (JMA-NHM), in order to investigate the mechanism of heavy rainfall events induced by mesoscale convective systems (MCSs). A horizontal resolution of the NHM-4DVAR is set to 2 km to resolve MCSs, and the length of the assimilation window is 1-hour. The control variables of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
80
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 71 publications
(80 citation statements)
references
References 19 publications
0
80
0
Order By: Relevance
“…Among others, much attention has been paid to skillful NWP for severe weather (e.g., Kain et al 2006, Hohenegger andSchär 2007a, b;Kawabata et al 2007;Roberts and Lean 2008). Recently, the ensemble Kalman filter (EnKF; Evensen 1994Evensen , 2003 has become a major method in data assimilation (DA), and has contributed to investigate convection-permitting regional NWP (e.g., Zhang et al 2007;Stensrud et al 2009Stensrud et al , 2013Clark et al 2010;Schwartz et al 2010;Baldauf et al 2011;Melhauser and Zhang 2012;Yussolf et al 2013, Kunii 2014a, Weng and Zhang 2016.…”
Section: Introductionmentioning
confidence: 99%
“…Among others, much attention has been paid to skillful NWP for severe weather (e.g., Kain et al 2006, Hohenegger andSchär 2007a, b;Kawabata et al 2007;Roberts and Lean 2008). Recently, the ensemble Kalman filter (EnKF; Evensen 1994Evensen , 2003 has become a major method in data assimilation (DA), and has contributed to investigate convection-permitting regional NWP (e.g., Zhang et al 2007;Stensrud et al 2009Stensrud et al , 2013Clark et al 2010;Schwartz et al 2010;Baldauf et al 2011;Melhauser and Zhang 2012;Yussolf et al 2013, Kunii 2014a, Weng and Zhang 2016.…”
Section: Introductionmentioning
confidence: 99%
“…Wulfmeyer et al, 2006;Kawabata et al, 2007), large deficiencies remain in quantitative precipitation forecasting (QPF) (e.g. Grams et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…The full model of JMANHM (Saito et al 2006;2012), which includes three-ice cloud microphysics without cumulus convection parameterization, was adopted as the forward model. The first version (v1) of the NHM-4DVAR considered perturbations only to dry dynamics and advection of water vapor (Kawabata et al 2007). Moreover, the second version (v2; Kawabata et al 2011) was implemented an additional warm rain process in the adjoint model (ADM).…”
Section: Nhm-4dvarmentioning
confidence: 99%
“…For more precise forecasts of thunderstorms, it is necessary to assimilate observations representing their environmental fields with both dynamical and thermodynamical information. Kawabata et al (2007) developed a cloud-resolving 4D-Var (NHM-4DVAR.v1), and expanded to assimilate observations of radar reflectivity, GPS slant total delay, and Doppler lidar (NHM-4DVAR.v2; Kawabata et al 2011;2013;. These studies showed that the NHM-4DVAR.v2 with these various observation operators has the ability to predict a thunderstorm with a scale approximately less than 50 km.…”
Section: Introductionmentioning
confidence: 99%